Improved raw starch amylase production by Saccharomyces cerevisiae using codon optimisation strategies. Issue 2 (10th December 2018) - Cripwell, Rosemary A; Rose, Shaunita H; Viljoen-Bloom, Marinda; van Zyl, Willem H
Abstract: Amylases are used in a variety of industries that have a specific need for alternative enzymes capable of hydrolysing raw starch. Five α-amylase and five glucoamylase-encoding genes were expressed in the Saccharomyces cerevisiae Y294 laboratory strain to select for recombinant strains that best hydrolysed raw corn starch. Gene variants of four amylases were designed using codon optimisation and different secretion signals. The significant difference in activity levels among the gene variants confirms that codon optimisation of fungal genes for expression in S. cerevisiae does not guarantee improved recombinant protein production. The codon-optimised glucoamylase variant from Talaromyces emersonii ( temG_Opt ) yielded 3.3-fold higher extracellular activity relative to the native temG, whereas the codon-optimised T. emersonii α-amylase ( temA_Opt ) yielded 1.6-fold more extracellular activity than the native temA . The effect of four terminator sequences was also investigated using temG and temG_Opt as reporter genes, with the ALY2 T terminator resulting in a 14% increase in glucoamylase activity relative to the gene cassettes containing the ENO1 T terminator. This is the first report of engineered S. cerevisiae strains to express T. emersonii amylase variants, and these enzymes may have potential applications in the industrial conversion of raw starch under fermentation conditions. Abstract : Several α-amylase and glucoamylase gene variants, designed using codon optimisation strategies, were expressed in Saccharomyces cerevisiae for improved protein production and increased amylolytic activity on raw starch.